2024
DOI: 10.46497/archrheumatol.2024.9814
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematics of the trunk, pelvis, hip, and knee during the single-leg squat and hip torque in subjects with isolated patellofemoral osteoarthritis compared to individually matched controls: Preliminary results

Cristiano Carvalho,
Fábio Viadanna Serrão,
Adalberto Felipe Martinez
et al.

Abstract: Objectives: This study aimed to compare three-dimensional kinematic of the trunk, pelvis, hip, and knee during the single-leg squat and hip torque in individuals with and without isolated patellofemoral osteoarthritis (PFOA). Patients and methods: This cross-sectional study evaluated trunk, pelvis, hip, and knee kinematics at 30°, 45°, and 60° knee flexion during the single-leg squat using the Vicon motion capture and analysis system, the Nexus System 2.1.1, and 3D Motion Monitor software. Sixteen individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Hence, we have no studies to compare our results with. Previous studies found non-significant differences between subjects with PF OA and controls regarding trunk kinematics on the sagittal plane during stair negotiation (Fok et al, 2013) and the descent phase of single-leg squat (Carvalho et al, 2024). This might explain why multifidus and TrA activation onset and duration are not significantly different between both groups, but prospective longitudinal studies are essential to ascertain this assumption.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hence, we have no studies to compare our results with. Previous studies found non-significant differences between subjects with PF OA and controls regarding trunk kinematics on the sagittal plane during stair negotiation (Fok et al, 2013) and the descent phase of single-leg squat (Carvalho et al, 2024). This might explain why multifidus and TrA activation onset and duration are not significantly different between both groups, but prospective longitudinal studies are essential to ascertain this assumption.…”
Section: Discussionmentioning
confidence: 91%
“…This finding is in line with the previous findings of Aminaka et al (2011) and Motealleh et al (2015). A recent study indicated that patients with isolated PF OA displayed significantly increased hip adduction at 30, 45, and 60 degrees of knee flexion during the descent phase of single-leg squat (Carvalho et al, 2024), which could be a speculative reason for the delayed onset of GM activation. Moreover, while the delayed onset of GM activation may have a role in the etiology of patellofemoral osteoarthritis, it is also possible that PF OA patients experience this delayed onset due to lowered activity as a pain-reduction strategy.…”
Section: Discussionmentioning
confidence: 99%